The Effect of Age on the Regenerative Potential of Human Eyelid Adipose-Derived Stem Cells - Mingqi Zhang; Zhuoshi Wang; Yan Zhao; Lirong Zhang; Ling Xu; Liu Cao; Wei He (Stem Cells International)
Human eyelid adipose-derived stem cells (HEASCs) are a new source of autologous mesenchymal stem cells, which are derived from neuroectoderm and potentially applied in the tissue regeneration and cell therapies. Based on the prevalence of blepharoplasty in Asia and the availability of HEASCs, we investigated the effect of donor age on their characteristics and regenerative potential of HEASCs in vitro. The HEASCs were isolated from patients of three groups: (1) <20 years (n=4), (2) >20 years, <45 years (n=5), and (3) >55 years (n=4). For each group, the proliferative capacity, colony-forming ability, surface markers, differentiation ability, wound healing function, and secreted protein were contrastively evaluated and quantified for statistical analysis. It was found that HEASCs were successfully isolated and cultured by an explant culture method. The proliferative rates, osteogenic and chondrogenic differentiation potentials, wound healing ability, and the expression of TGF-β1 and fibronectin protein of HEASCs significantly decreased as age increased. However, the expression of CD90 antigen and the adipogenic differentiation showed an age-related increase in HEASCs. As many degenerative diseases increase in prevalence with age, the age-related changes of the HEASCs proliferation potential, differentiation capacity, and wound healing ability should be taken into account whenever they are intended for use in research or cytotherapy.